Pengaruh Edukasi Kanker Payudara Terhadap Sikap WUS Dalam Melakukan SADARI di UPTD Puskesmas Rejosari Kabupaten Pringsewu - Rosmita Dini; Anissa Syafitri Almufaridin; Wulan Dari; Nila Qurniasih (Journal of Innovative and Creativity, 2025)
Breast cancer is one of the leading causes of death worldwide. It is estimated that 2.3 million women worldwide are diagnosed with breast cancer, and 670,000 die from it. Breast cancer education is needed to shape a more positive attitude among women of reproductive age (WRA). The demonstration method was chosen as an interactive and enjoyable educational approach that can encourage active participation from respondents, who are directly involved through observation, use, and discussion of the presented material, thus influencing attitude formation through various senses. This study aims to determine the effect of breast cancer education on the attitudes of women of reproductive age (WRA) in performing BSE (Breast Self-Examination) at the Rejosari Public Health Center (UPTD Puskesmas Rejosari). This study uses a quantitative method with a pre-experimental design, applying a one-group pretest-posttest design. The research sample consisted of 94 respondents, representing all WRAs at the UPTD Puskesmas Rejosari who met the inclusion and exclusion criteria. Data were collected using a questionnaire on the attitudes of WRAs towards performing BSE before and after receiving breast cancer education. Data analysis used the Wilcoxon test. The results showed that the average attitude of WRAs towards performing BSE before education was 67.0717, while after receiving education it increased to 72.6064. The Wilcoxon test showed a significant effect of breast cancer education using the demonstration method on the attitudes of WRAs in performing BSE (p-value < 0.001). The researcher suggests that there is a need for improved understanding of BSE techniques among WRAs and regular monitoring by health workers to ensure that the understanding and attitude of WRAs towards performing BSE techniques remain consistent.